Pendidikan Kesehatan Deteksi Dini Kesehatan Ibu Hamil dalam Mewujudkan Persalinan yang Aman Bagi Ibu dan Bayi - Nining Tunggal; Reni Tri Lestari; Isabella Rahmawati (Lembaga Pengembangan Kinerja Dosen, 2026)
Early detection of danger signs and complications is essential in maternal health to ensure safe childbirth for both mother and baby. This community service activity aimed to improve the knowledge and awareness of pregnant women regarding early detection of pregnancy-related health conditions at Kretek Primary Health Center, Bantul Regency. The activity involved 16 pregnant women as participants. The methods used included interactive lectures, discussions, question-and-answer sessions on recognizing danger signs, and simple screening through blood pressure measurement and mid-upper arm circumference (MUAC). Evaluation was conducted using pre-test and post-test assessments to measure participants' knowledge improvement. The results showed a significant increase in knowledge after the educational intervention. The average pre-test score of 61.25 increased to 96.25 in the post-test, with an average score improvement of 35 points. Participants also demonstrated active engagement throughout the activity, as reflected in their enthusiasm in asking questions and participating in discussions on pregnancy danger signs, the importance of antenatal care, and the role of family support in maintaining a healthy pregnancy. These findings indicate that health education delivered through a participatory approach and supported by educational media is effective in enhancing pregnant women's understanding. This activity is expected to strengthen pregnant women's preparedness in recognizing pregnancy risks early and support efforts to prevent complications, ultimately contributing to safe childbirth.